Gene Cloning, Sequencing, and Inactivation of the Branched-Chain Aminotransferase of Lactococcus lactis LM0230 - Atiles, Myrta W. (American Society for Microbiology, 2000)
A branched-chain aminotransferase gene (ilvE) from Lactococcus lactis LM0230 was identified on a 9-kb chromosomal insert by complementation in Escherichia coli DL39. Sequencing of a 2.0-kbp fragment resulted in the identification of a 1,023-bp open reading frame that could encode a 340-amino-acid protein. Sequence analysis of the deduced amino acid sequence revealed 62% identity to IlvE of Haemophilus influenzae and high similarity to IlvEs from a variety of organisms found in GenBank classified as class IV aminotransferases. Under logarithmic growth in complex medium, ilvE is transcribed monocistronically as a 1.1-kb transcript. Hydrophobicity plot analysis of the deduced amino acid sequence and the lack of a signal peptide sequence suggest IlvE is a cytosolic protein. A derivative of LM0230 lacking IlvE activity was constructed by gene replacement. Comparison of the IlvE-deficient strain's ability to grow in defined media lacking an amino acid but containing its α-keto acid biosynthetic precursor to that of the wild-type strain indicated that IlvE is the only enzyme capable of synthesis of Ile and Val from their biosynthetic precursors. Comparison of the aminotransferase activity of the IlvE mutant to LM0230 revealed that the mutant retained <2, 4.5, 43, 40, and 76% of its aminotransferase activity with Ile, Val, Leu, Met, and Phe, respectively. No difference in growth or acidification rate between LM0230 and the IlvE-deficient strain was observed in milk.